2015
DOI: 10.1002/asia.201500336
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Controlled‐Size Nanospheres inside Nanocavities of Self‐Organized Photopolymerizing Soft Oxometalates [PW12O40]n (n=1100–7500)

Abstract: The unusual self-assembly of {(BMIm)2 (DMIm)[PW12 O40 ]}n (n=1100-7500) (BMIm=1-butyl-3-methylimidazolium, DMIm=3,3'-dimethyl-1,1'-diimidazolium) soft oxometalates (SOMs) with controlled size and a hollow nanocavity was exploited for the photochemical synthesis of polymeric nanospheres within the nanocavity of the SOM. The SOM vesicle has been characterized by using several techniques, including dynamic light scattering (DLS), static light scattering (SLS), attenuated total reflection (ATR) IR spectroscopy, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…SOMs can undergo topological transformation, 51 can be used in patterning 52,53 and as active particles. 46 The catalytic activity of SOMs has also been explored in various types of reactions viz., in photo-polymerization [54][55][56] and photochemical water oxidation. 57 In this article we have shown that SOM type materials based on oxo-molybdate and oxo-tungstate clusters can efficiently catalyse the reduction of CO 2 to HCOOH/HCHO by transferring the electrons and protons generated from oxidation of water.…”
Section: Introductionmentioning
confidence: 99%
“…SOMs can undergo topological transformation, 51 can be used in patterning 52,53 and as active particles. 46 The catalytic activity of SOMs has also been explored in various types of reactions viz., in photo-polymerization [54][55][56] and photochemical water oxidation. 57 In this article we have shown that SOM type materials based on oxo-molybdate and oxo-tungstate clusters can efficiently catalyse the reduction of CO 2 to HCOOH/HCHO by transferring the electrons and protons generated from oxidation of water.…”
Section: Introductionmentioning
confidence: 99%
“…1 forms vesicle like superstructure in DMSO-water mixture. 53 The hydrodynamic radius of this vesicle can be controlled by changing the polarity of system. 53 We now synthesize a new composite material based on hydrocalumite and 1, and to do so we have added 1 (DMSO solution) in a dilute dispersion of hydrocalumite.…”
Section: Synthesis and Characterization Of [Bmimmentioning
confidence: 99%
“…Our group already reported that SOM can be synthesized from 1 which forms vesicle like superstructure in water dispersion. 53 Using this superstructure as photocatalyst we could synthesize polymeric spheres. But now we want to control the chain length of polyacrylic acid, using a two component SOM and an electroactive template which will facilitate the catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of the POM moiety on the electro active surface can enhance the catalytic activity of these materials ,. POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) . We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor ,…”
Section: Introductionmentioning
confidence: 96%